Serosurvey of Toxoplasma gondii and Toxocara spp. co-infection in pregnant women in low-income areas of Brazil - Pereira, Edlayne Larissa Gretter Machado; Ferreira, Isabella Braghin; Victorino, Roberta Brinholi; Lescano, Susana Angélica Zevallos; Giuffrida, Rogério; Kmetiuk, Louise Bach; Biondo, Alexander Welker; Santarém, Vamilton Alvares (Frontiers in Public Health, 2024)
Introduction: Despite human toxoplasmosis and toxocariasis have been listed amongst the top six most neglected parasitic zoonosis worldwide, presenting similar associated risk factors and transmission routes, few studies have been conducted in pregnant women and concurrent infection remains to be fully established. Accordingly, the present study has serologically assessed the coinfection and associated risk factors for Toxoplasma gondii and Toxocara spp. in pregnant women assisted by the public Unified National Health System (SUS) in southeastern Brazil. Materials and Methods: Blood samples were collected and tested for IgG antibodies against Toxoplasma gondii by chemiluminescence immunoassay and against Toxocara spp. by enzymelinked immunosorbent assay (ELISA). An epidemiological questionnaire was applied for gathering socioeconomic information to assess the risk factors associated to seropositivity for toxocariasis/toxoplasmosis by univariate analysis followed by logistic regression.